Symptom duration is associated with failure of periprosthetic joint infection treated with debridement, antibiotics and implant retention - Shao, Hongyi; Li, Rui; Deng, Wang; Yu, Baozhan; Yang, Dejin; Zhou, Yixin; Chen, Jiying (Frontiers in Surgery, 2022)
Background Debridement, antibiotics, and implant retention (DAIR) is an alternative treatment strategy for periprosthetic joint infection (PJI). However, no consensus exists regarding which patient population(s) may be most suitable for DAIR. This study aims to investigate the overall infection control rate and explore the prognostic factors associated with acute, hematogenous, and chronic PJIs treated with DAIR. Methods We retrospectively reviewed the included patients who were diagnosed with PJI and underwent DAIR at two institutions from 2009 to 2018 (n = 104). We collected the clinical data, including demographics, preoperative laboratory tests, Charlson Comorbidity Index, surgical information, and culture organism results. Treatment success was defined according to the criteria reported by Diaz-Ledezma. All patients were followed for at least one year unless failure preceded that time point. A multivariable analysis was utilized to identify prognostic factors associated with treatment, and a Kaplan-Meier survival analysis was used to depict the infection control rate. Results The overall treatment success rate in the current cohort of patients was 67.3% at a median 38.6 (interquartile range: 23.5, 90.7) months follow-up. Patients with a duration of infectious symptoms of more than ten days were more likely to fail (P = 0.035, hazard ratio 8.492, 95% confidence interval 1.159–62.212). There was no difference among acute, hematogenous, and chronic infections in terms of failure rate (P = 0.161). Conclusions DAIR is a reasonable treatment option for PJI, and its use in the setting of chronic infection does not appear to be a contraindication. Performing DAIR within ten days of the presentation of symptoms had a higher rate of treatment success.